A Case of Stenotic Change from Gastric Candidiasis Managed with Temporary Stent Insertion - Joo, Moon Kyung (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2011)
Invasive gastric Candida infection in patient with co-morbidity can cause stenotic change if it is developed at anatomically narrowing portion, such as distal antrum, pylorus, or duodenal bulb. However, proper management of benign stenosis by diffuse gastric Candidasis is still under controversy and palliative bypass surgery has several shortcomings because high risk operative group may be included in this case. Palliative placement of self-expandable metallic stent has been settled as a standard management of malignant gastric pyloric obstruction and it is expected to be applied in benign stenotic lesions due to its gradual dilation effect. We described a case of stenosis by diffuse gastric Candidasis at anastomosis of subtotal gastrectomy, which was managed by temporary placement of self-expandable metallic stent.